2004
DOI: 10.1017/s0252921100010654
|View full text |Cite
|
Sign up to set email alerts
|

Asteroseismology of the β Cep star ν Eri: initial results

Abstract: Abstract.We have acquired about 1200 hr of both spectroscopic and photometric measurements of the /3Cep star i/Eri with 22 telescopes around the world, detecting and identifying seven independent pulsation modes. They are the radial fundamental mode, an i = 1, gi triplet, an £ = 1, pi doublet and an I = 1, p2 singlet. Seismic model calculations by two independent teams suggest that it is not possible to explain the pulsational behaviour of «/Eri with standard stellar models. Some modifications of the input phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…It would thus be the second example of a star exhibiting two different types of pulsation. The high‐order g‐modes of the first such star, HD 209295, are however believed to be triggered by tidal effects (Handler et al 2002). As we have no evidence for binarity of ν Eri, it may therefore be the first star in which two types of pulsation with time‐scales more than an order of magnitude different are intrinsically excited.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It would thus be the second example of a star exhibiting two different types of pulsation. The high‐order g‐modes of the first such star, HD 209295, are however believed to be triggered by tidal effects (Handler et al 2002). As we have no evidence for binarity of ν Eri, it may therefore be the first star in which two types of pulsation with time‐scales more than an order of magnitude different are intrinsically excited.…”
Section: Discussionmentioning
confidence: 99%
“…Experience with δ Scuti stars has shown that the more the detection level for periodic light variations is pushed down, the more pulsation modes are detected (e.g. see the sequence of papers by Handler et al 1996, 1997, 2000). In fact, most of the pulsation modes of these stars have light amplitudes around or below 1 mmag, an amplitude quite easily detected with the large data sets of 2–3 mmag precision differential photometry obtained during these campaigns.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The research domain of asteroseismology has received a strong impetus since its successful application to the Sun (helioseismology), to several white dwarfs (for recent applications, see Vauclair et al 2002; Handler, Metcalfe & Wood 2002) and also to solar‐like stars (for a review, see Bedding & Kjeldsen 2003). So far, seismic studies have concentrated mainly on such stars because they have very rich frequency spectra consisting of short‐period oscillations.…”
Section: Introductionmentioning
confidence: 99%
“…The latter have been performed for many bright β Cephei stars (Aerts & De Cat 2003) but 16 (EN) Lac is one of the few multiperiodic objects for which both photometry and spectroscopy point towards the same mode identification for the detected non‐radial modes (Aerts et al 2003c). In an effort to improve this situation, and with the goal to perform the most in‐depth seismic application on a β Cephei star, Handler & Aerts (2002) set up a large spectroscopic and photometric multisite campaign for the star ν Eridani (HD 29248, V mag 3.92, spectral type B2 III). This campaign took place between 2002 October and 2003 January.…”
Section: Introductionmentioning
confidence: 99%